Mini-thoracotomy Approach for Heart Surgery in Tertiary Care Hospital of Nepal - Bhattarai, Anil; Shah, Sangam; Ranabhat, Kamal; Chand, Swati; Thapa, Sangharsha; Khakural, Prabhat (Journal of Nepal Health Research Council, 2024)
Background: The usual surgical technique for heart surgery has been median sternotomy, which provides excellent exposure of all cardiac structures and facilitates the establishment of cardiopulmonary bypass with central cannulation. A number of alternative surgical techniques, including the right anterolateral thoracotomy, posterolateral thoracotomy, and partial sternotomy, have been suggested. We want to share our experience with right anterior mini-thoracotomy versus right axillary mini-thoracotomy for closing an atrial septal defect.Methods: The study was a retrospective cross-sectional study conducted in a hospital. The study comprised patients with atrial septal defect admitted to Green City Hospital in Kathmandu, Nepal. From May 2016 until September 2021. Data was extracted to MS excel sheet, and then transported to the STATA version 17 for analysis. First, we computed descriptive analysis which included calculation of frequency, percentage, mean and median for presentation of socio-demographic variables. Continuous data were tested for normality using Shapiro-Wilk test.Results: A total of 25 patient were included in the study with median age 26 years (20-32). The median aortic cross clamp time was 25 minutes ranging 20-35 min. The median duration of cardiopulmonary bypass time ranging from 31to 161 minutes. The median time of Ax was 25 minutes and 26 minutes for right anterior mini-thoracotomy and right axillary mini-thoracotomy respectively. The median duration of hospital stay was 4 days ranging from 3-4 days. Nearly 36% study participants were associated with abnormal body mass index. (Either under nutrition or over nutritional status). Conclusions: There were no significant differences between the duration of intensive care unit and hospital stays, aortic cross clamp time, and complications between the two groups. However, the possibility of less blood loss during surgery and of cosmetic appearance in axillary incision is of special importance.Keywords: Heart surgery; mini-thoracotomy; Nepal; right anterior; right axillary.